Juridical Analysis of Minors Who Commit the Crime of Murder - Rizka Handayani Pohan; Rima Vania Ramadhani; Asmak UI Hosnah (JOURNAL OF ISLAMIC AND LAW STUDIES, 2024)
The aim of this research is to clarify the handling of criminal acts where the perpetrator is a minor, especially the crime of murder, and to clarify the application of the juvenile criminal justice system (SPPA) in prosecuting criminal acts committed by children. As a rule of law, Indonesia regulates all the lives of its citizens. country through applicable laws and regulations. The current laws do not provide justice to all Indonesian people without discrimination. As criminal acts committed by minors occur in society, especially in Indonesia, applicable law enforcement is different from criminal law in general. To overcome this problem, there is a special law that regulates it, SPPA (Juvenile Criminal Justice System). It would be more effective to use punitive sanctions and behavioral sanctions simultaneously (two-track principle). Efforts to divert at all stages of the investigation and limit prison sentences and recidivism. Article 8 concerns parties participating in diversion activities through advisory procedures and the diversion principles in Article 9.